The military orders and the diocesan bishops: a pragmatic relationship - Toomaspoeg, Kristjan (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2018)
The relations of the Military Orders with the bishops are a fundamental topic of their history. A lecture of the primary sources and of the existing secondary literature points out a very intricate system of relations between the orders and the diocesan powers. There are cases of a friendly alliance and of an enthusiastic support and collaboration, as well those of a pacific but “cold” coexistence, followed by a long series of conflicting relationships, issues and clashes, sometimes accompanied by physical violence, usurpations and sentences of excommunication. At the same time, the relations undergo an evolution and in every diocese the friendship could be transformed in conflict or vice versa. The paper intends to offer very short reflections on this topic, taking under observation some specific cases as those of the Kingdoms of Sicily and Portugal, but supported by examples coming from several eastern and western regions. The aim is to proceed with an attempt of classification of the relations between the orders and the clergy and to follow their general evolution, filling a gap in the general history of the Military Orders. The paper is articulated in three parts dedicated respectively to “friendly” relations with bishops, to conflicts and to mutual agreements.